Revitalisasi Rumah Baca Digital di Masa Pandemic - Gusna, Gusna; Yunisa Oktavia (Jurnal Ilmu Sosial dan Ilmu Politik, 2022)
Abstrack : Character education is education that is able to change attitudes, change mindsets and be able to follow current scientific and technological advances by getting used to the literacy culture here, it will not close the possibility of continuing to build the character of the next generation. Technological progress has become a major role, there are several things that play an important role in the progress of the times in this article. Building a digital-based reading house during a pandemic, there are several innovative and creative ideas that will be realized in order to achieve an educational vision and mission which is to educate the nation despite the circumstances. like today.